Church and Science: Developing Missionary Leadership in The Digitalization Era - Sirait, Rajiman Andrianus; Nainggolan, Alon Mandimpu; Novianti, Delpi (IAKN TORAJA, 2023)
Abstract: This study investigates the concept of missionary leadership in the digital age, as well as the associated challenges and adaptation strategies. Utilizing literature and the Bible as primary sources, the study utilizes a qualitative descriptive research design and a library research methodology. The objectives of this study are to explicate the concept of missionary leadership in the digital era and to investigate the problems and solutions associated with its adaptation. In light of technological advancements, the findings emphasize the significance of effective and pertinent missionary leadership. The church is encouraged to improve its technical, management, and communication skills in order to effectively carry out its mission in the digital landscape and meet the changing requirements of the congregation. By establishing a balance between the use of technology and personal relationships, the church can leverage digital platforms to advance its mission while remaining consistent with its core values. Keywords: Church, Digitalization, Missionary Leadership, Science. Abstrak: Studi ini menyelidiki konsep kepemimpinan misionaris di era digital, serta tantangan dan strategi adaptasi yang terkait. Dengan menggunakan literatur dan Alkitab sebagai sumber utama, penelitian ini menggunakan desain penelitian kualitatif yang bersifat deskriptif. Tujuan dari penelitian ini adalah untuk mendeskripsikan konsep kepemimpinan misionaris di era digital dan untuk menyelidiki masalah dan solusi yang terkait dengan adaptasinya. Dengan adanya kemajuan teknologi, temuan-temuan penelitian ini menekankan pentingnya kepemimpinan misionaris yang efektif dan relevan. Gereja didorong untuk meningkatkan keterampilan teknis, manajemen, dan komunikasinya agar dapat secara efektif menjalankan misinya dalam lanskap digital dan memenuhi kebutuhan jemaat yang terus berubah. Dengan membangun keseimbangan antara penggunaan teknologi dan hubungan pribadi, gereja dapat memanfaatkan platform digital untuk memajukan misinya sambil tetap konsisten dengan nilai-nilai intinya. Kata kunci: Digitalisasi, Gereja, Ilmu Pengetahuan, Kepemimpinan Misionaris.